Transcriptomic Analysis of the Early Strobilar Development of Echinococcus granulosus - Debarba, João Antonio (Pathogens, 2020)
Echinococcus granulosus has a complex life cycle involving two mammalian hosts. The transition from one host to another is accompanied by changes in gene expression, and the transcriptional events that underlie this transition have not yet been fully characterized. In this study, RNA-seq was used to compare the transcription profiles of samples from E. granulosus protoscoleces induced in vitro to strobilar development at three time points. We identified 818 differentially expressed genes, which were divided into eight expression clusters formed over the entire 24 h period. An enrichment of gene transcripts with molecular functions of signal transduction, enzymes, and protein modifications was observed upon induction and developmental progression. This transcriptomic study provides insights for understanding the complex life cycle of E. granulosus and contributes for searching for the key genes correlating with the strobilar development, which can be used to identify potential candidates for the development of anthelmintic drugs.